The dynamics of automation adoption: Firm-level heterogeneity and aggregate employment effects - Laura Bisio; Angelo Cuzzola; Marco Grazzi; Daniele Moschella (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
We investigate the impact of investment in automation-related goods on adopting and non-adopting firms in the Italian economy during 2011-2019. We integrate datasets on trade activities, firms', and workers' characteristics for the population of Italian importing firms and estimate the effects on adopters' outcomes within a difference-in-differences design exploiting import lumpiness in product categories linked to automation and AI technologies. We find a positive average adoption effect on the adopters' employment and on the value-added and average wage, whereas sales and productivity increase after an initial drop with a net positive effect five years after adoption. Crucially, the employment effect is heterogeneous across firms: a positive scale effect is predominant among small firms, whereas a negative displacement effect is predominant among medium and large firms. We complete the framework with a 5-digit sector-level analysis showing that adopting automation technologies has an overall negative effect on aggregate employment.
Keywords: D24; J23; L25; O33; 330; Automation; Employment; Firm heterogeneity; Imports; Technology adoption